Cognitive performance in patients with ischemic stroke and additional myocardial injury – results from the multicenter prospective observational PRAISE study - von Rennenberg, Regina; Litmeier, Simon; Szabo, Kristina; Mengel, Annerose; Petersen, Martina; Wunderlich, Silke; Michalski, Dominik; Thomalla, Götz; Kallmünzer, Bernd; Petzold, Gabor; Dichgans, Martin; Siepmann, Timo; et al. (Neurological Research and Practice, 2025)
Background: In the general population, cognitive impairment and dementia are more common in individuals with prior myocardial injury, defined as elevated levels of high-sensitive cardiac troponin (hs-cTn). In stroke patients, data on the link between myocardial injury and cognitive outcome are scarce. We aimed to analyze the association between the severity of myocardial injury (degree of hs-cTn elevation), presence of acute myocardial injury (dynamic change in elevated hs-cTn values > 20% in serial measurements) and cognitive performance over time after acute ischemic stroke. Methods: This is a prespecified analysis of the prospective multicenter observational PRediction of Acute coronary syndrome in acute Ischemic StrokE (PRAISE) study. PRAISE included 254 patients with an acute ischemic stroke or transient ischemic attack (TIA) and myocardial injury in 26 centers in Germany. Patients underwent cognitive assessment at baseline and before hospital discharge using the Montreal Cognitive Assessment (MoCA) and at three and twelve months after the index event using the Telephone Interview for Cognitive Status (TICS). We used linear regression to analyze the associations between cognitive performance and (1) severity of myocardial injury and (2) presence of acute myocardial injury. The association between hs-cTn and TICS scores over time was examined using inverse probability weighted generalized linear models. Results: Severity of myocardial Injury was associated with lower MoCA scores (adjusted beta − 2.6, 95% CI -4.0 - -1.2, p < 0.001) and higher proportion of cognitive impairment (i.e. MoCA score < 26 points) (adjusted OR 2.9, 95%CI 1.3–6.7, p = 0.012). Acute myocardial injury was associated with better cognitive performance (adjusted beta 1.8, 95% CI 0.4–3.1, p = 0.011). We found no association between hs-cTn and cognitive decline over twelve months. Conclusions: In patients with ischemic stroke, the severity of myocardial injury in general but not the presence of acute myocardial injury at time of stroke is associated with cognitive impairment. Trial registration: Clinicaltrials.gov NCT03609385 https://clinicaltrials.gov/study/NCT03609385?term=NCT03609385&rank=1 Date of registration 6th July 2018.
CRIS-Team Scopus Importer:2025-11-21